IMPLEMENTASI SOFT SKILL DAN HARD SKILL DALAM MENINGKATKAN KINERJA PEGAWAI DINAS PEMUDA DAN OLAHRAGA PROVINSI ( BENGKULU - Markoni Markoni (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
The problem in this study is how to implement Soft Skills and Hard Skills in improving the performance of the Bengkulu Province Youth and Sports Service (Dispora) Employees. Primary data needed was obtained through a questionnaire. Considering that the research population is diverse, the sample is taken using a stratified sampling technique. Data analysis used multiple regression and correlation methods, while the hypothesis test with t test and F test with 0.05.The results of the analysis show that Soft Skill and Hard Skill have an effect on employee performance, respectively 0.318 and 0.539. By comparing the two, the influence of Hard Skills on employee performance is more dominant when compared to the influence of Soft Skill changes.Soft Skills and Hard Skills together have a very strong relationship with employee performance with a variation contribution of 60.4%. Considering the contribution of the two types of expertise, it is recommended that the relevant officials make efforts to improve these skills, by conducting internal training, involving their employees in various trainings organized by other parties, and motivating their employees to continue to develop their skills independently.